Tumours in end-stage kidney - Hora, M; Hes, O; Reischig, T; Urge, T; Klecka, J; Ferda, J; Michal, M; Eret, V (Transplantation proceedings, 2008)
OBJECTIVE: Patients with end-stage kidney disease (ESKD) show a greater risk for renal cell carcinoma (RCC), which tends to be multifocal and bilateral. The malignant potential is unclear. The question is whether to remove both kidneys in patients with a tumor on one side only diagnosed by computed tomography (CT). MATERIALS AND METHODS: Kidney tumors were found in 14 patients with ESKD from January 2002 to December 2006. One was unfit for surgery. Thirteen patients underwent nephrectomy and 6 a bilateral procedure of whom only 2 had bilateral tumors on CT, 3 multiple tumors on the contralateral side, and 1 uncontrollable hypertension with tumors as an incidental finding. Tumors were found in all 19 specimens. RESULTS: In 13 kidneys (68.4%), the tumors were multiple; in 6 (31.6%), solitary. The types of tumor were: 13 (68.4%) papillary RCCs (PRCC), 9 (47.4%) clear RCCs (CRCC), a combination of PRCC and CRCC in 4 (21.0%), and myxoid liposarcoma (with solitary PRCC contralaterally). The mean follow-up was short (19 +/- 15 months; maximum, 54 months). Only 1 patient died due to a tumor at 16 months after operation. CONCLUSIONS: There is a high risk for bilateral involvement. Patients who undergo unilateral nephrectomy must be regularly followed and contralateral nephrectomy carefully considered, mainly in transplanted patients on immunosuppression. Further studies are needed to give a definitive answer about the indications for surgery and the indications for contralateral nephrectomy as well. To date, prophylactic contralateral nephrectomy should not be a therapeutic standard.
Keywords: nádory ledvin; Kidney Neoplasms; počítačová rentgenová tomografie; Kidney Failure, Chronic; Humans; lidé středního věku; Renal Dialysis; Female; Aged; dospělí; věkové faktory; dialýza ledvin; senioři; lidé; Sex Ratio; Adult; transplantace ledvin; staging nádorů; ženské pohlaví; chronické selhání ledvin; Male; Middle Aged; Tomography, X-Ray Computed; incidence; Incidence; Kidney Transplantation; karcinom z renálních buněk; Carcinoma, Renal Cell; Neoplasm Staging; Age Factors; poměr pohlaví; Risk Assessment; mužské pohlaví; hodnocení rizik